The Effect of LEAN Methodology on the Quality Management System of Land Drilling Companies. - Ali Malik, Al Harthy; Said M., Al-Saqri; Sagaran, Gopal; Asif, Mahbub Karim; Hock, Oo Yu (Research India Publications, 2018)
This paper presents the mediate effect of LEAN concept on the relationship between planning of drilling activities and overall performance (Quality Management System) among an Omani oil and gas drilling company. LEAN concept has been implemented in different industries with an overall objective to eliminate the waste from a define process. Hence, it is considered to be one of the key factors to improve and sustain the overall performance by a continual improvement mechanism. This paper presents a comprehensive assessment in the overall performance of a drilling rig before and after implementing LEAN concept in one main critical drilling activity known as tripping connection. The overall trend of time and cost (before and after implementing LEAN) is determined.